To solve this system of equations, we can use the method of elimination.
First, let's rewrite both equations in standard form:
2x + 8y = 8
2x - 4y = -16
Now, we can eliminate x by subtracting the second equation from the first equation:
(2x + 8y) - (2x - 4y) = 8 - (-16)
2x + 8y - 2x + 4y = 8 + 16
12y = 24
Now, divide both sides by 12 to solve for y:
y = 24 / 12
y = 2
Now that we have found the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
2x + 8(2) = 8
2x + 16 = 8
2x = -8
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 2.
2x +8y = 8
2x - 4y = -16
1 answer